Technology-Supported Art as a "Way to Participation" - Molly Bathje MS, OTR/L (Scholarworks @ WMU, 2014)
Brianna Vitale provided the painting featured on the cover of the Spring 2014 issue of The Open Journal of Occupational Therapy. Brianna completed the painting, titled "Flamingo," using a mouth joystick (joust) to draw the image on her computer and an assistive device to translate her computer artwork into the watercolor painting. At 12 years old, Brianna has been living for the past 9 years with tetraplegia, the result of a spinal cord injury (SCI). Through technology and with the support of family, friends, and health care professionals, Brianna energetically engages in a variety of creative, social, and philanthropic activities.